Peony diagram modeling for improving the easy disassembly design of mobile electronic products - Junling Huang; Chuangchuang Cui; Wei Jiang; Libin Zhu (Scientific Reports)
Abstract Designing mobile electronic products for easy disassembly is crucial for promoting resource recycling. However, many current approaches overlook the need to consider the disassembly of parts from the perspective of the overall product structure and practical recycling requirements, leading to potentially suboptimal or unnecessary optimization strategies. This study introduces a novel visual disassembly information model called the “Peony Diagram.” This model uses a multi-layer ring diagram to depict part hierarchies and constraint relationships and employs specific symbols to convey part disassembly information and highlight key components. The difficulty of disassembling individual parts is assessed by calculating difficulty coefficients based on quantified disassembly information in the model. To validate the model’s effectiveness, a smartphone was used as a case study to determine the shortest disassembly sequence and evaluate disassembly difficulty for both single and multiple parts. The findings demonstrate that the proposed method can accurately assess the ease of disassembly of key components during product repair and recycling. Consequently, it can suggest strategies to enhance recycling and disassembly efficiency and reduce the difficulty of disassembling critical parts.